Revisions in written composition: Introducing speech-to-text to children with reading and writing difficulties - Kraft, Sanna (Frontiers in Education, 2023)
The ability to perform revisions targeting the content of the text is important for text quality improvement, and it is hypothesized that lower-level transcription processes need to be automatized in order to free up capacity for higher-level processes such as revision. However, for people with reading and writing difficulties due to underlying difficulties with decoding and spelling, the transcription process is rarely automatized because of their troubles with spelling. One possible way to circumvent spelling difficulties, and possibly gaining capacity for higher level processes such as revision, is to write using speech-to-text (STT). This study investigates the revisions performed when children with reading and writing difficulties (n = 16), and a reference group without such difficulties (n = 12), compose text using STT and using a keyboard. More specifically, the study investigates whether, and if so how, revisions at various levels, errors left in the final text product, and text quality differ between conditions and between groups. The compositions were logged using keystroke logging (keyboard) and audio- and screen-recording (STT). The level of revisions were manually coded. The results showed that children with reading and writing difficulties gain more from composing with STT compared to keyboard than the reference group. They leave fewer errors in their final text product when composing by means of STT, even though they need to engage more in the correction of surface errors because of the large number of STT errors. Despite the numerous STT errors, neither the proportion of meaning-related revisions nor text quality decreased in composing with STT (for either of the groups). Taken together, the results suggest, albeit not emphatically, that STT may be appropriate as a facilitatory tool for children with reading and writing difficulties. However, more research is needed to investigate instruction that addresses strategies for STT transcription and highlights the shortcomings of the tool in the target language, and also focuses specifically on higher-level aspects of composition such as planning or revising, in order to gain further knowledge about the feasibility of using STT as a means of composition for children who struggle with writing, and its possible effects over time.